Elevated β1-Adrenergic Receptor Autoantibody Levels Increase Atrial Fibrillation Susceptibility by Promoting Atrial Fibrosis - Shang, Luxiang; Zhang, Ling; Shao, Mengjiao; Feng, Min; Shi, Jia; Dong, Zhenyu; Guo, Qilong; Xiaokereti, Jiasuoer; Xiang, Ran; Sun, Huaxin; Zhou, Xianhui; Tang, Baopeng (Frontiers in Physiology, 2020)
Objective: Beta 1-adrenergic receptor autoantibodies (β1ARAbs) have been identified as a pathogenic factor in atrial fibrillation (AF), but the underlying pathogenetic mechanism is not well understood. We assessed the hypothesis that elevated β1ARAb levels increase AF susceptibility by promoting atrial fibrosis. Methods: A total of 70 patients with paroxysmal AF were continuously recruited. The serum levels of β1ARAb and circulating fibrosis biomarkers were analyzed by ELISA. Linear regression was used to examine the correlations of β1ARAb levels with left atrial diameter (LAD) and circulating fibrosis biomarker levels. Furthermore, we established a rabbit β1ARAb overexpression model. We conducted electrophysiological studies and multielectrode array recordings to evaluate the atrial effective refractory period (AERP), AF inducibility and electrical conduction. AF was defined as irregular, rapid atrial beats > 500 bpm for > 1000 ms. Echocardiography, hematoxylin and eosin staining, Masson's trichrome staining, and picrosirius red staining were performed to evaluate changes in atrial structure and detect fibrosis. Western blotting and PCR were used to detect alterations in the protein and mRNA expression of TGF-β1, collagen I and collagen III. Results: Patients with a LAD ≥ 40 mm had higher β1ARAb levels than patients with a smaller LAD (8.87 ± 3.16 vs. 6.75 ± 1.34 ng/mL, P = 0.005). β1ARAb levels were positively correlated with LAD and circulating biomarker levels (all P < 0.05). Compared with the control group, the rabbits in the immune group showed the following: (1) enhanced heart rate, shortened AERP (70.00 ± 5.49 vs. 96.46 ± 3.27 ms, P < 0.001), increased AF inducibility (55% vs. 0%, P < 0.001), decreased conduction velocity and increased conduction heterogeneity; (2) enlarged LAD and elevated systolic dysfunction; (3) significant fibrosis in the left atrium identified by Masson's trichrome staining (15.17 ± 3.46 vs. 4.92 ± 1.72%, P < 0.001) and picrosirius red staining (16.76 ± 6.40 vs. 4.85 ± 0.40%, P < 0.001); and (4) increased expression levels of TGF-β1, collagen I and collagen III. Conclusion: Our clinical and experiential studies showed that β1ARAbs participate in the development of AF and that the potential mechanism is related to the promotion of atrial fibrosis.